Giant symptomatic gastric lipoma: A case report and literature review. (2018) - Amundson, Julia R.; Straus, David; Azab, Basem; Liu, Sandy; Garcia Buitrago, Monica T.; Yakoub, Danny
Highlights: Gastric lipomas may become symptomatic when ≥10 cm, at which point they are classified as giant gastric lipomas. Giant gastric lipomas are extremely rare, with only 6 prior cases reported in the English worldwide literature since 1980. Gastric lipoma density is similar to peripheral fat on CT, −80 to −120 Hounsfield units, which is nearly pathognomonic. Circumferential excision of gastric lipomas with a clear margin of normal tissue is adequate for symptomatic resection. Preservation of gastric continuity via gastrotomy and primary closure avoids complications of gastrojejunostomy. Abstract: Introduction: Lipomas are uncommon tumors of the gastrointestinal tract; gastric lipomas account for <1% of all gastric tumors encountered (Nickloes and Sutphin [1]). Giant gastric lipomas, defined as ≥10 cm, are exceedingly rare with only 6 cases reported since 1980 (Cappell et al., Termos et al., Singh et al., Ramaraj et al., Rao et al., Priyadarshi et al., Neto et al. [3–9]). We hereby present a case of a giant gastric lipoma that became symptomatic seven years after its initial identification and was excised preserving gastric continuity. Case presentation: Our patient is a 58-year-old African American male with a 3 cm gastric mass incidentally found on CT in 2010. In September of 2017, the patient presented with severe epigastric pain, nausea, and vomiting. Abdominal CT scan revealed an increase in size of the patient's gastric lesion to 7.2 × 10.3 × 7.3 cm. He underwent an exploratory laparotomy with transverse anterior gastrotomy and primary closure. Pathologic examination revealed a 12 cm submucosal, well-circumscribed, non-encapsulated mass comprised of mature adipose tissue without atypia or mitotic figures, consistent with lipoma. Discussion: The majority of gastric lipomas are asymptomatic, identified on CT scan as round/ovoid masses with low attenuation and homogenous appearance, measuring −80 to −120 Hounsfield units. These findings are nearly pathognomonic. Due to the benign nature of gastric lipomas, circumferential excision with a clear margin of normal tissue is adequate for symptomatic resection. This is the second report of giant gastric lipoma excised with continuity preserving partial gastrectomy, avoiding gastrojejunostomy complications. Conclusion: Fatty tumors are rare in the gastrointestinal tract, yet lipomas must be on the differential when masses are found with Hounsfield units similar to peripheral fat.